The spillover effects of economic policy uncertainty on Turkish Unemployment - Ahmet Güney; Mustafa Karakuş; Nuriye Güneyi (İktisat Politikası Araştırmaları Dergisi)
Türkiye is a small open economy with free capital mobility; therefore, it may be subject to international transmission of economic policy uncertainty shocks. This study seeks to determine whether foreign economic policy uncertainties drive unemployment fluctuations in Türkiye. We investigate the spillover effects of global and regional economic policy uncertainty indexes and local variables on the Turkish labour market. The study’s main findings show that unemployment is the highest net information receiver under full and rolling sample analysis. The findings also indicate that United States policy uncertainty affects interest rates and inflation through the capital channel. In contrast, European Union and Germany-induced effects affect industrial production and unemployment through the trade channel. The effect of policy uncertainty in EU countries is stronger on unemployment. Local factors influence unemployment more than global factors. Taking steps to control local factors would be beneficial for employment continuity by policymakers.